PEMIKIRAN KALAM MAULANA MUHAMMAD ALI - Zainuddin Hamkah (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2020)
Muhammad Ali is a rationalist theologian who has been able to display the face of Islamic understanding and thought logically. Maulana was one of the reformers who violently dynamized Muslims through the door of ijtihad. He promoted rational thinking through the Lahadi Ahmadiyya missionary movement in his popular work, The Religion of Islam, so that his religious movements could be accepted in parts of Europe including London. Even with the spirit of rationalization, he dismissed the mythological understanding of the teachings of Islam, synergistic with the occurrence of modernization in Europe which proclaimed demythologization. As a reflection, thoughts on the words of Maulana Muhammad Ali are synergistic with scientific enthusiasm, although at a certain level it is still difficult to break away from apologetics. This is still very reasonable because this study has a theological nuance, especially when it is related to the scope of the kalam study, which is to defend the faith from the attack of non-Muslim thoughts. However, at least we put the pattern of thinking about Maulana as an important part in the effort to dynamize Muslims so that they will not be trapped by myths (Israiliyat).